Strategi pengembangan literasi anak melalui program Getuk Golan di Dinas Perpustakaan dan Kearsipan Kabupaten Ponorogo - Ridwan, Mat; Sugianto, Alip; Riyanto, Riyanto (FPPTI Jawa Tengah, 2025)
This study aims to describe the strategy for developing children's literacy through the Getuk Golan program (Gerakan Bertutur, Games, Outbound, dan Literasi Anak), initiated by the Library and Archives Office of Ponorogo Regency as an effort to address the low reading interest index among children. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed using the Miles, Huberman, and Saldana model. The findings reveal that Getuk Golan is a community-based literacy innovation that integrates storytelling, educational games, outbound activities, and parental involvement in a fun and participatory learning atmosphere. The program not only improves reading and writing skills but also develops children's socio-emotional and cultural literacy through direct interaction in public spaces. The uniqueness of the program lies in its holistic approach that combines cognitive, affective, social, and cultural dimensions in an integrated manner, which differs from previous studies focusing only on a single method. This study concludes by recommending the replication of the Getuk Golan program in other regions as a strategic model for strengthening community-based children's literacy culture. Keywords: children’s literacy; Getuk Golan; literacy strategy; library; Ponorogo